Implement of Students Result by Using Genetic Algorithm - katiyar, Abhishek; Pandey, Anil (International Journal of Computer Sciences and Engineering, 2019)
The artificial intelligence technique such as Genetic algorithm plays a significant role for handling in many fields such as artificial intelligence, engineering, robotic, etc. This is the technique to evaluate the new populations from natural population and provide the best result generation to generation. This is applied in students’ quantitative data analysis to identify the most impact factor in their performance in their curriculum. The results will help the educational institutions to improve the quality of teaching after evaluating the marks achieved by the students’ in academic career. This student analysis model considers the quantitative factors such as compiler, automata, data structure and other departmental marks to find the most impacting factor using genetic algorithm.